Post-exercise hot water immersion induces heat acclimation and improves endurance exercise performance in the heat - Zurawlew, M. J.; Walsh, N. P.; Fortes, M. B.; Potter, C. (Scandinavian Journal of Medicine & Science in Sports, 2016)
We examined whether daily hot water immersion (HWI) after exercise in temperate conditions induces heat acclimation and improves endurance performance in temperate and hot conditions. Seventeen non-heat-acclimatized males performed a 6-day intervention involving a daily treadmill run for 40 min at 65% V?O2max in temperate conditions (18 °C) followed immediately by either HWI (N = 10; 40 °C) or thermoneutral (CON, N = 7; 34 °C) immersion for 40 min. Before and after the 6-day intervention, participants performed a treadmill run for 40 min at 65% VO2max followed by a 5-km treadmill time trial (TT) in temperate (18 °C, 40% humidity) and hot (33 °C, 40% humidity) conditions. HWI induced heat acclimation demonstrated by lower resting rectal temperature (Tre, mean, -0.27 °C, P < 0.01), and final Tre during submaximal exercise in 18 °C (-0.28 °C, P < 0.01) and 33 °C (-0.36 °C, P < 0.01). Skin temperature, Tre at sweating onset and RPE were lower during submaximal exercise in 18 °C and 33 °C after 6 days in HWI (P < 0.05). Physiological strain and thermal sensation were also lower during submaximal exercise in 33 °C after 6 days in HWI (P < 0.05). HWI improved TT performance in 33 °C (4.9%, P < 0.01) but not in 18 °C. Thermoregulatory measures and performance did not change in CON. Hot water immersion after exercise on 6 days presents a simple, practical, and effective heat acclimation strategy to improve endurance performance in the heat.